Insulin and Autophagy in Neurodegeneration - de Mello, Natália Prudente; Orellana, Ana Maria; Mazucanti, Caio Henrique; de Morais Lima, Geovanni; Scavone, Cristoforo; Kawamoto, Elisa Mitiko (Frontiers in Neuroscience, 2019)
Crosstalk in the pathophysiological processes underpinning metabolic diseases and neurodegenerative disorders have been the subject of extensive investigation, in which insulin signalling and autophagy impairment demonstrate to be a common factor in both conditions. Although it is still somewhat conflicting, pharmacological and genetic strategies that regulate these pathways may be a promising approach for aggregate protein clearancing and consequently the delaying of onset or progression of the disease. However, as the response due to this modulation seems to be time-dependent, finding the right regulation of autophagy may be a potential target for drug development for neurodegenerative diseases. In this way, this review focuses on the role of insulin signalling/resistance and autophagy in some neurodegenerative diseases, discussing pharmacological and non-pharmacological interventions in these diseases.